1987
DOI: 10.1111/j.1464-5491.1987.tb00910.x
|View full text |Cite
|
Sign up to set email alerts
|

Guar Sprinkled on Food: Effect on Glycaemic Control, Plasma Lipids and Gut Hormones in Non‐insulin Dependent Diabetic Patients

Abstract: The effects of guar granules sprinkled over food on carbohydrate and lipid metabolism were studied in a double-blind cross-over trial in 18 patients with non-insulin-dependent diabetes mellitus (mean +/- SEM age 61.3 +/- 2.5 years). Five-gram guar granules (Guarem, Rybar Laboratories, Amersham, Bucks) were sprinkled over food at each main meal for 4 weeks, and during a 4-week placebo period (separated by a 2-week 'wash-out' period), 5 g wheat bran was taken in the same way. Diabetic treatment was not changed d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

1988
1988
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(27 citation statements)
references
References 25 publications
0
27
0
Order By: Relevance
“…In previous studies, guar gum (Aro et al, 1981;Fuessl et al, 1987;Groop et al, 1993) as well as other sources of soluble fiber (Vuksan et al, 1999;Chandalia et al, 2000;Pins et al, 2002) have been reported to result in either a significant or a nonsignificant decrease in blood or plasma glucose concentrations. There were no significant differences in GHbA1c between the groups.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…In previous studies, guar gum (Aro et al, 1981;Fuessl et al, 1987;Groop et al, 1993) as well as other sources of soluble fiber (Vuksan et al, 1999;Chandalia et al, 2000;Pins et al, 2002) have been reported to result in either a significant or a nonsignificant decrease in blood or plasma glucose concentrations. There were no significant differences in GHbA1c between the groups.…”
Section: Discussionmentioning
confidence: 93%
“…Increased intake of soluble fiber has been found to improve glucose homeostasis and postprandial glucose metabolism (Fuessl et al, 1987;Groop et al, 1993). Guar gum is the most widely studied form of soluble fiber.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several authors report no modifications in glycaemia or a modest improvement of glycaemic control (Botha et al, 1981;Carroll et al, 1981;Lim et al, 1990;Stahl & Berger, 1990), while others indicate significant decreases (Smith & Holm, 1982;Fuessl et al, 1987;Chuang et al, 1992;Fairchild et al, 1996;Gatenby et al, 1996;Brenelli et al, 1997), some of them similar to the value indicated in this paper (10.1%, Chuang et al, 1992a, b) and others higher (50%, Fuessl et al, 1987;35%, Brenelli et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Several later studies showed that guar gum improves both glycemic and blood lipid levels in diabetes. 10,11,[13][14][15][16] Guar is a non-cellulose, soluble dietary fiber that is extracted from the cluster bean. The most effective mode of guar administration is to mix it with food.…”
Section: Fpg and Hbal Values Are Shown Inmentioning
confidence: 99%